The effect of parental divorce on the psychological well-being of muslim youth: implications for counseling and psycho-theraphy - Orcullo, Daisy Jihan; Ismail, Nik Ahmad Hisham (Institut Terjemahan dan Buku Malaysia, 2016)
Experiences and perceptions of Muslim children from divorced parents. Study and their traumatic experiences and impact of their parents' divorce on their faith and spiritual comfort.